Imaging Spatial Distribution of Photogenerated Carriers in Monolayer MoS2with Kelvin Probe Force Microscopy - Yim, Woongbin; Nguyen, Van Tu; Phung, Quynh Thi; Kim, Hwan Sik; Ahn, Yeong Hwan; Lee, Soonil; Park, Ji Yong (ACS Applied Materials and Interfaces, 2022)
The spatial distribution of photogenerated carriers in atomically thin MoS2flakes is investigated by measuring surface potential changes under light illumination using Kelvin probe force microscopy (KPFM). It is demonstrated that the vertical redistribution of photogenerated carriers, which is responsible for photocurrent generation in MoS2photodetectors, can be imaged as surface potential changes with KPFM. The polarity of surface potential changes points to the trapping of photogenerated holes at the interface between MoS2and the substrate as a major mechanism for the photoresponse in monolayer MoS2. The temporal response of the surface potential changes is compatible with the time constant of MoS2photodetectors. The spatial inhomogeneity in the surface potential changes at the low light intensity that is related to the defect distribution in MoS2is also investigated.
Keywords: Change-points; Kelvin probe force microscopy; Light illumination; Photocurrent generations; Photogating; Photogenerated carriers; Photogenerated holes; Photoresponses; Polarity of surfaces; Potential change; interface; Kelvin probe force microscopy; MoS2; photogating; photoresponse